2013
DOI: 10.1002/anie.201304695
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Mode‐Specific Vibrational Autodetachment from Dipole‐Bound States of Cold Anions

Abstract: Molecules with sufficiently large dipole moments were predicted to form weakly bound negative ions in the dipolar field [1][2][3][4] and such dipole-bound anions have been observed and characterized experimentally. [5][6][7][8][9][10] Negative ions with dipolar molecular cores can have excited dipole-bound states (DBSs) near the detachment threshold, analogous to Rydberg states in neutral molecules. DBSs in excited anions were first observed as resonances in photodetachment crosssections. [11][12][13] Ultrahig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
191
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(219 citation statements)
references
References 38 publications
27
191
1
Order By: Relevance
“…This is the main character of DBSs of anions observed previously. 36,39 Hence, features 1 and 2 are due to the 14 ′1 0 and 8 ′1 0 vibrational levels, respectively, of the excited DBS of CH 3 COO − , as we expected.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…This is the main character of DBSs of anions observed previously. 36,39 Hence, features 1 and 2 are due to the 14 ′1 0 and 8 ′1 0 vibrational levels, respectively, of the excited DBS of CH 3 COO − , as we expected.…”
supporting
confidence: 71%
“…[33][34][35] However, the studies of autodetachment dynamics of DBSs were hindered by congested spectra at room temperature. Recently, we directly observed mode-specific vibrational autodetachment from DBSs of cold phenoxide anions, 36 which were cooled in a temperature-controlled ion trap to eliminate vibrational hot bands and minimize rotational broadening. The ∆v = −1 vibrational propensity rule, which was initially developed for autoionzation from Rydberg states 37 and extended to autodetachment, 38 was directly observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gunion et al 39 and more recently Liu et al 62 found autodetachment in the photoelectron spectroscopy of phenoxide.…”
Section: Discussionmentioning
confidence: 96%
“…The double arrows below the images indicate the laser polarization. 150 the DBS ground state by resonant two-photon detachment. The binding energy of the DBS was measured to be 97 cm −1 relative to the detachment threshold at 18 173 cm −1 , i.e., the EA of phenoxy.…”
Section: B Resonant Pe Imaging and Spectroscopy Of Cold Phenoxide VImentioning
confidence: 99%